1996
DOI: 10.1177/104063879600800413
|View full text |Cite
|
Sign up to set email alerts
|

Water Hemlock (Cicuta Douglasii) Toxicoses in Sheep: Pathologic Description and Prevention of Lesions and Death

Abstract: Abstract. Water hemlock causes numerous livestock losses in North America every year. Description of pathologic and serum biochemical changes has been lacking in the literature. Tubers of western water hemlock (Cicuta douglasii) induced excessive salivation, tremors, grand mal seizures, skeletal and cardiac myodegeneration, and death in sheep given 1.2-2.7 g fresh tuber/kg body weight by gavage. Seizures were intermittent with periods of relaxation until death occurred from anoxia during seizure activity. In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Diagnosis of water hemlock poisoning can be made by documenting plant exposure from rumen or stomach contents. In surviving animals, elevated serum LDH, AST, and CK from seizure induced muscle damage peaks by 3 days after exposure then declines within 8-10 days after exposure (82).…”
Section: Plant and Animal Biomarkers For Water Hemlock Poisoningmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of water hemlock poisoning can be made by documenting plant exposure from rumen or stomach contents. In surviving animals, elevated serum LDH, AST, and CK from seizure induced muscle damage peaks by 3 days after exposure then declines within 8-10 days after exposure (82).…”
Section: Plant and Animal Biomarkers For Water Hemlock Poisoningmentioning
confidence: 99%
“…Animals that survive acute intoxication do not have any lasting effects. Death normally occurs within 1-8 h after consuming the plant(82).…”
mentioning
confidence: 99%
“…Four experienced only discomfort; however, one individual who ate two roots and another who ate one root developed grand mal -type seizures within 1 hour. The sheep recovered partially within 12 hours and completely in several days to a week (Panter et al 1996). The other individual, who had eaten one root, had fi ve seizures of 2 minutes duration each over a period of 3 hours.…”
Section: Cicuta Lmentioning
confidence: 99%
“…Although water hemlock poisoning has many features of a cholinergic toxidrome, an animal study found that water hemlock-induced seizures were not suppressed by pretreatment with anticholinergic agents benztropine or biperiden, nor worsened by the cholinergic agonist physostigmine, but were well controlled with diazepam [46,47]. In an animal study, Panter et al [48] found that in sheep given 1.5-2.5 times the lethal dose of water hemlock (C. douglasii) by gavage, intravenous administration of sodium pentobarbital at the onset of the first seizure prevented further seizures and skeletal and cardiac muscle degeneration and resulted in rapid and complete recovery [48].…”
Section: Treatmentmentioning
confidence: 99%